MEDIASI SEBAGAI PENGUATAN KEARIFAN LOKAL BANYUMAS DALAM PENYELESAIAN PERKARA PIDANA - Taufiq, Muhammad; Sarsiti, Sarsiti; Widyaningsih, Rindha; Hendriana, Rani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
This Â study is discussed about the mediation mechanism based on the local wisdom in Banyumas and factors inhibiting in the implementation. This study used a qualitative sociological juridical approach. The results showed that the mechanism for the resolution of criminal cases through mediation based on the value of local wisdom in Banyumas can be done outside and within the criminal justice, while still empowering the use of social network mediator. The mediation mechanism outside the criminal justice is done when the criminal case has not been reported or filed to the police, while the mechanism in the criminal court is done when a criminal case has been reported or filed with the police, and each of these mechanism has a sequence of stages. Meanwhile, the voluntary mediation became the first and man choices of Banyumas people. Inhibiting factors in the implementation of the mediation is primarily related to substantial and cultural components.